Quality improvement methodology can reduce hospitalisation for abscess management. Issue 10 (11th January 2022) - Dunn, Michael; Savoie, Kate; Erdem, Guliz; Dykes, Michael W; Buckingham, Don; Spencer, Sandra; Besner, Gail; Kenney, Brian
Abstract : Background: Abscesses are a common reason for ED visits. While many are drained in the ED, some require drainage in the operating room (OR). We observed that a higher percentage of patients at our institution in Columbus, Ohio, were admitted to the hospital with abscesses for incision and drainage (I&D) in the OR than other institutions, including paediatric institutions. Our aim was to decrease hospitalisations for abscess management. Methods: A multidisciplinary team convened to decrease hospitalisation for patients with abscesses and completed multiple 'Plan-Do-Study-Act' cycles, including increasing I&Ds performed in the ED. Other interventions included implementation of a clinical pathway, training of procedure technicians (PT), updating the electronic medical record (EMR), credentialing advanced practice nurses in sedation and individual follow-up with providers for admitted patients. Data were analysed using statistical process control charts. Gross average charges were assessed. Results: Admissions for I&D decreased from 26.3% to 13.7%. Abscess drainage in the ED improved from 79.3% to 96.5%. Mean length of stay decreased from 19.5 to 11.5 hours for all patients. Patients sedated increased from 3.3% to 18.2%. The number of repeat I&Ds within 30 days decreased from 4.3% to 1.7%. Conclusion: We decreased hospitalisations for abscess I&D by using quality improvement methodology. The most influential intervention was an initiative to increase I&Ds performed in the ED. Additional interventions included expanded training of PTs, implementation of a clinical pathway, updating the EMR, improving interdepartmental communication and increasing sedation providers.